Pitfalls in Intraocuar Pressure Measurement by Goldmann-Type Applanation Tonometers - Asad Jamal Dar, Fiaz, Amjad Akram, Amir Yaqub (Pakistan Journal of Ophthalmology, 2009)
In recent years, Applanation tonometry using the Goldmann instrument has become the gold standard in the assessment of intraocular pressure. Unfortunately, it is often not recognized that there are numerous sources of error that may significantly influence accuracy of Goldmann-type Applanation tonometers. It is very important that the clinician should be able to keep in mind these potential pitfalls while checking intraocular pressure.